- PERTANGGUNGJAWABAN PELAKSANA TUGAS DIREKSI ATAS PERJANJIAN BISNIS REFERRAL ASURANSI : - - Ilma Zhafirah Albar; Arif Wicaksana (Faculty of Law, Universitas Trisakti, 2023)
There could still be a vacancy on the Board of Directors while it fulfills its obligations and functions. The Acting Director (Plt.) of the Board of Directors is the member of the Board of Directors who fills in for absent Board members. All decisions made by the members of the Board of Directors he replaces may be made by the Acting Board of Directors. How to assess the agreements between the Plt. Board of Directors in a Limited Liability Company in UUPT and the Plt. Board of Directors on the liabilities of PT AJTM is how the issue is formulated. Normative research, which is descriptive and analytical and is based on secondary data, is the research methodology. It is qualitative analysis. namely real behavior and conclusions are drawn deductively. The results of the research and discussion illustrate that Plt. The Board of Directors is only implicitly regulated in the Company Law because their role is basically the same as the Board of Directors. Responsibility for the legal relationship that has existed between PT AJTM and third parties cannot be suspended to members of the board of directors individually, because the cooperation agreement made by a legal entity is carried out on behalf of the Company itself as a legal entity, not on behalf of individuals. In this case it can be concluded that a third party can sue PT AJTM for their rights if they have not been fulfilled.